Catalytic Activity of Urchin-like Ni nanoparticles Prepared by Solvothermal Method for Hydrogen Evolution Reaction in Alkaline Solution. (10th February 2017) - Abbas, Syed Asad; Iqbal, Muhammad Ibrahim; Kim, Seong-Hoon; Jung, Kwang-Deog
Graphical abstract: Highlights: Urchin-like Ni is prepared in solvothermal reaction. Urchin-like Ni is formed via Ni(OH)2 aggregates in ethanol and oleylamine. Exchange current density of urchin-like Ni is 0.191 mA cm −2 . Urchin-like Ni exceeds the catalytic performance of commercial Pt/C in HER. Abstract: Ni nanoparticles with different morphologies were synthesized for hydrogen evolution reaction (HER) in alkaline solution. Here, Ni(acac)2 was converted into Ni metal nanoparticles in solvothermal reactions with simple alcohols and oleylamine (OAm). The morphology of the resulting Ni nanoparticles was dependent mainly on the OAm/Ni molar ratio in alcohol solvent. Aggregates of spherical Ni nanoparticles (NiEt-OAm1) were observed at the OAm/Ni molar ratio of 1.0, whereas two echinoid Ni nanoparticles (NiEt-OAm4 and NiEt-OAm6) could be prepared in ethanol at the OAm/Ni molar ratios of 4.0 and 6.0. Ni(OH)2 formed in ethanol during a reaction time of 5 h was then reduced into echinoid Ni nanoparticles after 8 h. Echinoid Ni nanoparticles were formed by atomic addition on the tops of the multipod Ni particles formed via Ni(OH)2 /NiO aggregates. Webbed feet-like particles (NiIPA-OAm4) with plate edges were also observed in isopropanol under the same reaction conditions. The catalytic activities of the prepared Ni nanoparticles for the hydrogen evolution reaction were evaluated in alkaline solution. The NiEt-OAm4 with urchin-like morphology was much more active than the NiIPA-OAm4 with webbed feet-like morphology. The exchange current density of Ni catalysts was increased with increasing the OAm/Ni molar ratio. The NiEt-OAm6 exhibited an exchange current of 0.191 mA cm −2 and the NiEt-OAm4 exceeded electrocatalytic performance of a commercial Pt catalysts (40% Pt on Vulcan XC 72) in a stability test for 100 kiloseconds at −1.5 V (vs. Hg/HgO) in 1.0 M NaOH due to its high stability.